Anemia ibu hamil pada perokok pasif Di wilayah puskesmas kota banjarmasin tahun 2016 - hapisah hapisah; tri tunggal (Jurnal Skala Kesehatan, 2019)
Anaemia in pregnancy increases the risk of complications in pregnancy and childbirth, e.i. maternal death, prematurity, LBW, and perinatal mortality. Many factors cause anaemia, including when pregnant woman got exposure from tar, free radicals and carbonmonoxide contained in cigarette smoke that is inhaled directly by unintentionally. CO is directly bound in maternal hemoglobin so the ability of hemoglobin to be much greater binds CO than oxygen. Inhaling tobacco smoke in passive smoking, has far lower levels of folic acid, exposure to acid smoking causes a disruption of iron metabolism in red bloodcells. Iron very useful in the formation of hemoglobin, deficiencies of folic acid and iron can cause defects in the fetus and anaemia. Research purpose to know the incidence of anaemia in pregnant women passive smokers in Banjarmasin City Health Center 2016. Research method uses a case control study design. Population is all pregnant women in Banjarmasin City Health Center 2016. Samples were 120 people, composed of 60 cases pregnant women anaemia, and control were 60 pregnant women anaemia which doesn’t meet the criteria of inclusion and exclusion. Results showed 36 pregnant women were exposed to cigarette smoke, 24 respondents (40%) had a case group and 12 respondents (20%) in control group. There is a meaningful relationship between pregnant women passive smokers with incidence of anemia, value of p = 0.028 0.05 and OR α < 2.67 (CI-6.034 1.178). Exposure to cigarette smoke are at risk of 2.67 times against the incidence of anaemia pregnant woman than not exposed. Keywords: passive smokers, anemia in pregnancy